An Urban Scheme for the ECMWF Integrated Forecasting System: Global Forecasts and Residential CO2 Emissions. (2nd March 2023) - McNorton, J.; Agustí‐Panareda, A.; Arduini, G.; Balsamo, G.; Bousserez, N.; Boussetta, S.; Chericoni, M.; Choulga, M.; Engelen, R.; Guevara, M.
Abstract: The impact of urbanization on local weather patterns affects over half the global population. Global numerical weather prediction systems have reached a resolution at which urban conurbations can be spatially resolved, justifying their representation within land surface parameterizations with the aim of improving local predictions. Additionally, real‐time atmospheric monitoring of trace gas emissions can utilize weather variables relevant for urban areas. We investigated whether a simple single‐layer urban canopy scheme can be used within a global forecast model to jointly improve predictions of near‐surface weather variables and residential CO2 emissions. The scheme has been implemented in the Integrated Forecast System used operationally at the European Centre for Medium‐Range Weather Forecasts running at ∼9 km horizontal resolution. First, we selected a suitable urban land cover map (ECOCLIMAP‐SG) based on comparisons with regional data and land surface temperature MODIS retrievals. The urban scheme is verified by providing improved 2 m temperature (∼10%) and 10 m wind (∼17%) RMSE values for both summer and winter months around urban environments. The influence of the scheme was most noticeable at night. Additionally, we have implemented a simple temperature‐dependent residential emissions model to calculate real‐time CO2 heating emissions. These were validated against existing offline products, national reporting and by comparing atmospheric simulations with total column CO2 observations. The results show an improved temporal variability of emissions, which arise from synoptic scale temperature changes. Given the improved predictability from the urban scheme for both weather and emissions, it will be operationally implemented in an upcoming model cycle. Plain Language Summary: In urban areas, temperatures are often elevated due to an effect known as the urban heat island. Although global weather forecasts, generated using computer models, typically include a representation of land surface processes, they often do not include the urban environment. We implemented a relatively simple urban scheme in the model of the European Centre for Medium‐Range Weather Forecasts and selected an appropriate urban cover map to use by comparing forecast land temperatures with satellite observations. We then compared this scheme with observations from urban sites around the globe and found improved temperature and wind forecasts. Furthermore, we used information from the urban scheme to generate a global forecast of residential CO2 emissions from heating. We find that by forecasting these emissions using the weather model we improve our prediction of atmospheric CO2 concentrations around urban environments. Key Points: Several urban land cover maps were evaluated using satellite land‐surface temperature retrievals and independent data At ∼9 km horizontal resolution, an urban scheme improves modeled 2 m temperature and 10 m wind forecasts over urban areas of varying size An online residential heating CO2 emissions model (Modeling Emissions from Heating in Near‐real‐time Driven by the Integrated Forecasting System) using model variables improves forecasts of atmospheric concentrations